Dietary supplementation with functional amino acids improves the capacity of growing pigs to cope with a health challenge - França, I. [UNESP] (2024)
This study aimed to assess the effects of additional dietary supplementation with a blend of functional amino acids (FAA) with Thr, Trp, and Met as a preventive (prior to health challenge), curative strategy (during health challenge) or both targeting the performance, body composition, metabolic biomarkers of growing group-housed pigs raised under a health challenge. Additionally, the influence of these feeding strategies on pig response was investigated after the challenge (during the finishing phase). Sixty weaned piglets [6.3 ± 0.9 kg body weight (BW)] were distributed based on BW in a nursery barn to one of two dietary treatments (n = 30): control (CN) or supplemented with FAA blend (FAA+; 120 % of the Thr:Lys, Trp:Lys, and Met+Cys:Lys requirements) for 7 weeks. After 7 weeks, the pigs (27.9 ± 4.2 kg of BW) were distributed in a randomized complete block design to one of four treatments for the period of the health challenge period in the growing phase: pigs fed a CN diet during the nursery period were either maintained on a CN diet (control; n = 14) or switched to an FAA+ diet (curative strategy; n = 14), whereas the pigs fed an FAA+ diet during the nursery period were either fed a CN diet (preventive strategy; n = 14) or continued receiving an FAA+ diet (continuous strategy; n = 14). The health challenge consisted of subjecting growing pigs to batch mixing, poor housing conditions, and oral inoculation with Salmonella Typhimurium (ST). Poor housing conditions were maintained for 4 weeks (weeks 8–11). After this period, the pigs received the same standard diets for 9 weeks (weeks 12–20), and the facilities were cleaned daily. The health challenge increased the rectal temperature (P < 0.01) and serum concentrations of haptoglobin (P < 0.05), IgA (P < 0.05), IgG (P < 0.01), triglycerides (P < 0.01), creatinine (P < 0.01), and urea (P < 0.01), while reducing serum concentrations of lactate dehydrogenase (P < 0.01), albumin (P < 0.01), and glucose (P < 0.05). Pigs fed a continuous FAA+ diet trend towards lower fecal ST shedding (P < 0.10) than did the curative strategy pigs and had better fecal consistency scores (P < 0.01) than did the control pigs. During the challenge period, pigs fed FAA+ curatively or continuously demonstrated higher average daily gain and feed efficiency compared to control pigs (P < 0.01). Greater (P < 0.05) protein deposition (+30 %) and improved (P < 0.05) nitrogen retention efficiency (+20 % to curative and +30 % to continuous strategies) were observed in the pigs fed the FAA+ diet during the health challenge compared with the control pigs. Curative-fed FAA+ pigs had greater BW at the end of the finishing phase than did the control and preventive group (P < 0.05). In conclusion, the use of FAA supplementation as a curative or continuous strategy is highly effective at improving the performance and body composition of growing pigs under a health challenge.